The complete chloroplast genome of Euphorbia hirta (Euphorbiaceae), a commonly used medicinal plant in China. Issue 8 (3rd August 2021) - Zhang, Yancheng; Lu, Zhaocen; Zhang, Deng; Li, Jingjian
Abstract: Plants in the genus Euphorbia have been widely used as herbal medicine, and for ornamental horticulture and biofuel production. In this study, we report the complete chloroplast genome of Euphorbia hirta which is known as the 'asthma-plant' due to its medicinal use. The chloroplast genome of this species is 164, 340 bp in length, including a pair of inverted repeat regions (IRs) (27, 354 bp) that are divided by a large single-copy region (LSC) (91, 373 bp) and a small single-copy region (SSC) (18, 259 bp). The chloroplast genome of E. hirta contains 111 unique genes (77 protein-coding, 30 tRNA, and four rRNA ), 19 of which are duplicated in the IR regions. The overall GC content is 35.4%. Phylogenetic analysis fully resolved E. hirta groups with other species of Euphorbia . The complete chloroplast genome of E. hirta provides useful information that can be used to distinguish related species and reconstruct evolutionary relationships.